2003
DOI: 10.1101/gad.1115203
|View full text |Cite
|
Sign up to set email alerts
|

GATA-3: an unexpected regulator of cell lineage determination in skin

Abstract: Multipotent skin stem cells give rise to epidermis and its appendages, including the hair follicle. The Lef-1/Tcf family of Wnt-regulated transcription factors plays a major role in specification of the hair shaft, but little is known about how the equally important hair channel, the inner root sheath (IRS), develops in concert to shape and guide the hair. In a microarray screen to search for transcriptional regulators of hair follicle morphogenesis, we identified GATA-3, a key regulator of T-cell lineage dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
278
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(302 citation statements)
references
References 63 publications
21
278
1
2
Order By: Relevance
“…In none of the 37 pathological skin conditions investigated expression of GA-TA-3 was observed. The finding of GATA-3 expression in the matrix of the hair follicle is consistent with a study by Kaufman CK et al (14), which has shown that this transcription factor is essential for stem cell lineage determination in skin and for directing epidermal stem cells to become inner root sheath cells. Furthermore, GATA-3-null embryos show aberrations in hair follicle morphogenesis that include not only structural defects in the inner root sheath and in the hair shaft, but also molecular defects in cell lineage determination (14).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In none of the 37 pathological skin conditions investigated expression of GA-TA-3 was observed. The finding of GATA-3 expression in the matrix of the hair follicle is consistent with a study by Kaufman CK et al (14), which has shown that this transcription factor is essential for stem cell lineage determination in skin and for directing epidermal stem cells to become inner root sheath cells. Furthermore, GATA-3-null embryos show aberrations in hair follicle morphogenesis that include not only structural defects in the inner root sheath and in the hair shaft, but also molecular defects in cell lineage determination (14).…”
Section: Resultssupporting
confidence: 80%
“…The finding of GATA-3 expression in the matrix of the hair follicle is consistent with a study by Kaufman CK et al (14), which has shown that this transcription factor is essential for stem cell lineage determination in skin and for directing epidermal stem cells to become inner root sheath cells. Furthermore, GATA-3-null embryos show aberrations in hair follicle morphogenesis that include not only structural defects in the inner root sheath and in the hair shaft, but also molecular defects in cell lineage determination (14). Although GA-TA-3 has been recently described to be localized in the spinous layer of the interfollicular epidermidis (16), in our study we didn't find the expression of GATA-3 in the spinous layer probably because of the different technique used.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…2). GATA-3 is an important mediator of skin and hair development [47], although its specific function in epidermal development and differentiation has not yet been established. However, Np63 can transactivate IKK only indirectly via GATA-3 (Fig.…”
Section: Transcriptional Activities Of P63 Isoformsmentioning
confidence: 99%
“…GATA3 regulates lineage determination of many cell types. These include neurons of the sympathetic nervous system, T helper cells, the inner root sheath of hair follicles, fat cells, nephritic ducts of the kidney, and the ear cochleae [4,5]. Fetal mice cannot survive to term without GATA3 [6].…”
Section: Introductionmentioning
confidence: 99%